Field notes contributed by Dennis L. Carter, August 1, 1996 - Carter, Dennis L.et al (1996)
List of birds and locations contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1996. Epson - sheet feed/flatbed